2011
DOI: 10.2174/092986711797200408
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anticonvulsants for Possible Use in Neuropathic Pain

Abstract: Neuropathic pain is a kind of pain related with functional abnormality of neurons. Despite large progress in pharmacotherapy, neuropathic pain is still considered an unmet need. Nowadays, there are few drugs registered for this condition, such as pregabalin, gabapentin, duloxetine, carbamazepine, and lidocaine. Among them, pregabalin, gabapentin and carbamazepine are well known antiepileptic drugs. Among the group of new antiepileptic drugs, which are addressed to 1% of human world population suffering from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 164 publications
(180 reference statements)
0
38
0
1
Order By: Relevance
“…Fig. (8 [26,37]. Although well established position in pharmaceutical market, its mechanism of action is not yet completely understood.…”
Section: Phenytoin (Pht)mentioning
confidence: 99%
See 3 more Smart Citations
“…Fig. (8 [26,37]. Although well established position in pharmaceutical market, its mechanism of action is not yet completely understood.…”
Section: Phenytoin (Pht)mentioning
confidence: 99%
“…Molecular modeling showed that the pharmacophore segments of CBZ and PHT are similar, and CBZ is also able to develop interaction with binding site in domain IV-S6 [46]. CBZ is used in the treatment of simple partial, complex partial and generalized tonic-clonic seizures but it is not effective against absence seizures [26,37].…”
Section: Phenytoin (Pht)mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, VPA is widely used as a mood-stabilizer in bipolar disorder [2], in the treatment of schizophrenia [3], neuropathic pain [4] as well as migraine headache prophylaxis [5]. Due to its beneficial activity in reducing the incidence of both generalized and partial seizures in adults and children, the drug belongs to the so called "first-line" anticonvulsive agents and belongs to the most often prescribed antiepileptic drugs.…”
Section: Introductionmentioning
confidence: 99%